Representação da mulher no livro didático do ensino médio : a construção da figura feminina dentro do gênero poema - Tavares, Jeny Machado do Val (2022)
Women’s representation within the society has been reaching visibility in different communication fields, producing research about that representation, and seeking to understand how it works in multiple social, political, and educational spaces. The present study walks towards this direction, and from the enunciative-discursive perspective it aims to investigate about the way women are represented in high school textbook poems, since the notice of the National Book and Didactic Material Program (PNLD) from 2018 instructs that texts must treat the female figure in an empowered manner. This study is linked to the Literacy and School Education Research Group (ALFALE), from the research line “Linguagens, cultura e construção do conhecimento: perspectivas histórica e contemporânea”, of the Postgraduation in Education program, from the Federal University of Mato Grosso, Rondonópolis Campus (PPGEdu/CUR/UFMT), and its broad goal is to investigate the female figure constitution from the analysis of the poem genre present in the collection of didactic books (DBs) of the Portuguese Language (PL) for high school (HS) - Português contemporâneo: diálogo reflexão e uso, by Cereja, Vienna and Damien (2016). Furthermore, this research aimed to discuss issues about the text and its production contexts, in a discursive perspective, with the purpose of developing the theoretical base of investigation and analysis; to identify in the didactic book poems linguistic aspects related to women characteristics; and to understand in which way the female figure is represented in the poem utterances. The chosen methodology for this investigation was based in the documentary and qualitative approach, because the poems included in the collection selected for this research were described and analyzed. Moreover, the theoretical contribution was supported by the enunciative-discursive of Bakhtin and the Circle, dialoguing with the concepts of concrete utterance, extraverbal context and discourse genres. When approaching genre as a teaching practice, it was used, particularly, Marcuschi (2008), among other authors who deal with the importance of this subject in school. Regarding the literary genre poem, the contributions of Candido (2006) and Moisés (2003) were sought. Finally, the official documents of the Ministério da Educação (MEC) and the theoreticalconceptual discussions of scholars such as Bezerra (2020) and Batista (2003) contributed to the dialogues about the theoretical basis that constitute the DB. Results show that the poem genre, present in the DBs collection, instigates reflections about the social issues related to women and demands a dialogic position of the teacher so that this critical analysis reverberates in the development of their students.